The Influence of Organizational Change and Organizational Culture on Teacher Performance at XYZ High School in Bekasi City - David; Anggraini Mudjiono, Sherina; Winadi Prasetyoningtyas, Ari Anggraini (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyze the influence of Organizational Change and Organizational Culture on Teacher Performance at SMA XYZ in Bekasi City. A quantitative research method was employed, with data collected through questionnaires distributed to teachers. Data analysis was conducted using multiple linear regression tests and partial significance tests (t-tests) to determine the individual effects of each variable. The results show that Organizational Change has a positive and significant effect on Teacher Performance. Conversely, Organizational Culture does not affect Teacher Performance. The Adjusted R² value of 0.165 indicates that Organizational Change and Organizational Culture collectively explain 16.5% of the variation in Teacher Performance, while the remaining 83.5% is influenced by other factors outside this research model. Based on these findings, it is recommended that SMA XYZ continue to strengthen organizational change programs to enhance teacher performance, and further develop organizational culture initiatives to achieve a greater impact on performance outcomes.